A Modified Transverse Process-Pedicle Approach Applied to Unilateral Extrapedicular Percutaneous Vertebroplasty. (22nd October 2021) - Zhuo, Yunyun; Liu, Liehua; Wang, Haoming; Li, Pei; Zhou, Qiang; Liu, Yugang
Abstract : Objective . To introduce a modified transverse process-pedicle puncture technique applied to unilateral extrapedicular percutaneous vertebroplasty (PVP) for the treatment of osteoporotic lumbar vertebral compression fractures. Methods . A retrospective study was performed on 91 patients with osteoporotic vertebral compression fractures (OVCFs) who underwent unilateral extrapedicular PVP from June 2016 to September 2018. Lumbar and back pain was assessed through the visual analogue scale (VAS). Function recovery was assessed through the Oswestry disability index (ODI). Radiologic outcomes were assessed mainly on the basis of bone cement distribution and anterior vertebral height. Results . A total of 101 fractured vertebrae were successfully treated using the extrapedicular technique without any recognized clinical complications. The postoperative VAS and ODI values were significantly lower than the corresponding preoperative values P < 0.01 . Radiologic outcomes in all fractured vertebrae showed that the diffusion of bone cement could exceed the midline of the vertebral body. There was no significant difference between preoperative and postoperative anterior vertebral heights P < 0.05 . Conclusion . The modified transverse process-pedicle approach applied to unilateral extrapedicular percutaneous vertebroplasty is a simple, safe, and effective surgical method.